2004
DOI: 10.1016/j.jml.2003.08.003
|View full text |Cite
|
Sign up to set email alerts
|

The preparation of syllables in speech production

Abstract: Models of speech production assume that syllables play a functional role in the process of word-form encoding in speech production. In this study, we investigate this claim and specifically provide evidence about the level at which syllables come into play. We report two studies using an odd-man-out variant of the implicit priming paradigm to examine the role of the syllable during the process of word formation. Our results show that this modified version of the implicit priming paradigm can trace the emergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
92
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 42 publications
3
92
3
Order By: Relevance
“…1; CCVV, Exp. 2), Cholin et al (2004) found a significantly larger preparation effect for constant sets as compared to variable sets. The authors argue that this preparation effect, which cannot be attributed to a segmental overlap effect, offers strong evidence for the relevance of syllables in word form encoding.…”
Section: Empirical Evidence For Syllabic Units In Speech Productionmentioning
confidence: 83%
See 1 more Smart Citation
“…1; CCVV, Exp. 2), Cholin et al (2004) found a significantly larger preparation effect for constant sets as compared to variable sets. The authors argue that this preparation effect, which cannot be attributed to a segmental overlap effect, offers strong evidence for the relevance of syllables in word form encoding.…”
Section: Empirical Evidence For Syllabic Units In Speech Productionmentioning
confidence: 83%
“…In a recent study, Cholin, Schiller, and Levelt (2004) used an odd man out variant (Janssen, Roelofs, & Levelt, 2002) of the implicit priming technique to demonstrate that speakers can benefit from a shared syllable structure. In this study, subjects learned sets of prompt-target pairs.…”
Section: Empirical Evidence For Syllabic Units In Speech Productionmentioning
confidence: 99%
“…Segment-toframe association is the process that lends the necessary flexibility to the system depending on the speech context . After the segments have been associated with the metrical frame, the resulting phonological syllables may be used to activate the corresponding phonetic syllables in a mental syllabary (Cholin, Levelt, & Schiller, in press;Cholin, Schiller, & Levelt, 2004;Crompton, 1981;Levelt, 1989Levelt, , 1992Levelt & Wheeldon, 1994;Schiller, Meyer, Baayen, & Levelt, 1996;Schiller, Meyer, & Levelt, 1997). Once the syllabic gestural scores are made available, they can be translated into neuro-motor programs, which are used to control the movements of the articulators, and then be executed resulting in overt speech (Goldstein & Fowler, 2003;Guenther, 2003;Schiller, van Lieshout, Meyer, & Levelt, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Syllables in the syllabary may possibly be represented in terms of gestural scores (Browman & Goldstein, 1992) specifying articulatory motor programs for syllable-sized chunks. Although there is very little on-line evidence for the use of syllables in speech production (Ferrand, Segui, & Grainger, 1996;Ferrand, Segui, & Humphreys, 1997;but see Brand, Rey, & Peereman, 2003;Schiller, 1998Schiller, , 2000Schiller, Costa, & Colome, 2002), the idea of having precompiled syllabic motor programs is very attractive because it decreases the computational load of the phonological/phonetic encoding component (Cholin, Schiller, & Levelt, 2004;Crompton, 1981;Levelt & Wheeldon, 1994; for lexico-statistical support see Schiller, Meyer, Baayen, & Levelt, 1996).…”
Section: Introductionmentioning
confidence: 99%